The wishing pool and other stories - Due, Tananarive, 1966- (Akashic Books, 2024)
"In her first new book in seven years, Tananarive Due further cements her status as a leading innovator in Black horror and Afrofuturism American Book Award-winning author Tananarive Due's second collection of stories ranges from horror to science fiction to suspense. From the mysterious, magical town of Gracetown to the aftermath of a pandemic to the reaches of the far future, Due's stories all share a sense of dread and fear balanced with heart and hope. In some of these stories, the monster is racism itself; others address the monster within, or other universal struggles set against the supernatural or surreal. All of them are written with Due's trademark attention to detail and deep characterization. In addition to previously published work, this collection contains brand-new stories, including "Rumpus Room," a supernatural horror novelette set in Florida about a woman's struggle against both outer and inner demons"--